2017
DOI: 10.2106/jbjs.16.00311
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Increases the Rate of Reoperation for Infection within 90 Days After Primary Total Joint Arthroplasty

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
8
56
0
Order By: Relevance
“…Similar to the present study, they also found that smokers had higher rate of multiple medical problems. 2 Our study found that smokers had an average increased inpatient cost of approximately $1100 per patient. It is also important to emphasize that this cost is only an approximation.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Similar to the present study, they also found that smokers had higher rate of multiple medical problems. 2 Our study found that smokers had an average increased inpatient cost of approximately $1100 per patient. It is also important to emphasize that this cost is only an approximation.…”
Section: Discussionmentioning
confidence: 58%
“…There are several factors that increase the rate of complications following total joint arthroplasty including but not limited to diabetes, obesity, alcohol consumption, and other medical comorbidities. 2,3 Smoking has emerged as another factor associated with high complication rates after total joint arthroplasty. 2,[4][5][6][7][8][9] It is estimated that 16.8% of adults smoked cigarettes in 2014 10 and up to 24% of total joint arthroplasty patients smoke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the variables that have been shown to affect the outcome after total joint replacement include social and demographic characteristics, medical comorbidities, and surgical technique [3][4][5][6][7]. Areas of continued active research include the effect of intrinsic factors such as obesity [8][9][10], cardiovascular disease [11,12], mental health disorders [13•, 14-17•, 18•, 19], hepatic disease [20, 21•, 22, 23•, 24], nutritional deficiencies [25-29•, 30], bone metabolic disease [31][32][33][34][35][36][37], and diabetes mellitus [38•, 39, 40], as well as external factors such as nicotine use [41,42], recent corticosteroid injections [43][44][45][46][47], and discharge disposition [48,49]. The goal of this article is to review the most recent literature, published within the last 3 years, regarding a selection of patient-specific factors that may influence This article is part of the Topical Collection on Quality and Cost Control in TJA outcomes following total joint arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…2016, Tischler et al. 2017). However, these observations were not consistent between the different studies, with some studies reporting no effect of smoking on these same outcome measures (Inoue et al.…”
mentioning
confidence: 99%